People Behavior Related To The Spread Of Covid-19’s Hoax - Christiany Juditha (BBPSDMP KOMINFO MAKASSAR, 2020)
Covid-19 became the biggest non-natural disaster in the world in 2020. It first broke out in Wuhan, China, and then spread to other countries including Indonesia. The public is in uncertainty and receives a lot of information about Covid-19 through various media. This condition is exacerbated by the spread of hoax related to Covid-19 which is difficult to contain. The purpose of this study was to analyses society's behavior related to the spread of the Covid-19 hoax. This research uses a survey method with a quantitative approach. The results of the study concluded that respondents' knowledge about Covid-19 and hoax was very adequate. However, most respondents are hesitant and are in a position that can sometimes distinguish hoax, sometimes not because of the large amount of information obtained every day. The public panic at Covid-19 caused hoax to continue to be spread in the hope that the information could be useful in preventing and treating. While the respondents did not spread Covid's-19 hoax, because they considered the information to be incorrect, not useful, and harmful to the health of others, and they wanted to break the chain of hoax distribution to themselves.